Evaluation of ECDC Influenza-like illness (ILI) case definition to detect respiratory syncytial virus (RSV) infection through the Influenza Surveillance System in Portugal, 2010-2018 - Sáez-Lopes, Emma (2019)
INSA-DDI em colaboração com Emma Sáez-López (programa EUPHEM) e INSA-DEP.